2013
DOI: 10.2310/8000.2013.130726
|View full text |Cite
|
Sign up to set email alerts
|

Photodocumentation as an emergency department documentation tool in soft tissue infection: a randomized trial

Abstract: Objectives: Current documentation methods for patients with skin and soft tissue infections receiving outpatient parenteral anti-infective therapy (OPAT) include written descriptions and drawings of the infection that may inadequately communicate clinical status. We undertook a study to determine whether photodocumentation (PD) improves the duration of outpatient treatment of skin and soft tissue infections. Methods: A single-blinded, prospective, randomized trial was conducted in the emergency departments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Overall, the methodological quality of the studies varied: 30% (11/37) of the studies met ≤60% of the criteria outlined by the MMAT (lower methodological quality), and 70% (26/37) of the studies met >60% of the criteria (higher methodological quality) [ 26 ]. Reviewers’ ratings for each methodological quality criterion are presented in Multimedia Appendix 2 [ 28 - 33 , 35 - 39 , 41 - 46 , 49 - 51 , 54 - 66 , 68 , 73 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the methodological quality of the studies varied: 30% (11/37) of the studies met ≤60% of the criteria outlined by the MMAT (lower methodological quality), and 70% (26/37) of the studies met >60% of the criteria (higher methodological quality) [ 26 ]. Reviewers’ ratings for each methodological quality criterion are presented in Multimedia Appendix 2 [ 28 - 33 , 35 - 39 , 41 - 46 , 49 - 51 , 54 - 66 , 68 , 73 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Providers from diverse fields use photography to record clinical findings. Physicians have reported that photo documentation improves their patient assessment and enhances confidence in clinical decision-making [ 4 ]. Patients also perceive the value of photographs and generally approve of the use of clinical images in medical records and coordination of care [ 4 , 5 ], a practice that can help avoid repeated or uncomfortable examinations.…”
Section: Background: Value Of Photo Documentationmentioning
confidence: 99%
“…Physicians have reported that photo documentation improves their patient assessment and enhances confidence in clinical decision-making [ 4 ]. Patients also perceive the value of photographs and generally approve of the use of clinical images in medical records and coordination of care [ 4 , 5 ], a practice that can help avoid repeated or uncomfortable examinations. Integration of clinical images when communicating with specialists has also been shown to improve the accuracy of the diagnosis [ 3 , 6 ].…”
Section: Background: Value Of Photo Documentationmentioning
confidence: 99%
“…These studies, alongside our own experiences, support the hypothesis that using PMD for clinical photography is widespread among Australian surgical services, although no dedicated literature exists. Benefits of clinical photography include monitoring of pathology, expedited specialist review for patients in remote settings and limiting the need for patients to repeatedly expose sensitive anatomy 3 . A study investigating the use of clinical photography for monitoring treatment‐response in superficial skin infections found that 65% of physicians reported improved decision‐making capacity when utilizing clinical photography 3 .…”
Section: Prevalence and Benefits Of Clinical Photographymentioning
confidence: 99%
“…Benefits of clinical photography include monitoring of pathology, expedited specialist review for patients in remote settings and limiting the need for patients to repeatedly expose sensitive anatomy 3 . A study investigating the use of clinical photography for monitoring treatment‐response in superficial skin infections found that 65% of physicians reported improved decision‐making capacity when utilizing clinical photography 3 . Clinical photographs are not limited to patient anatomy and can include photographs of drains, catheters and radiographical images.…”
Section: Prevalence and Benefits Of Clinical Photographymentioning
confidence: 99%